Implikasi Kebijakan Izin Lingkungan Terhadap Lingkungan Hidup Di Indonesia - Muryati, Dewi Tuti; Triasih, Dharu; Mulyani, Tri (Universitas Semarang, 2022)
The purpose of this study is to analyze the implications of environmental permit policies on the environment in Indonesia. The urgency of this research is given that the environmental permit policy is a government tool that is preventive in nature, controlling people's behavior, and repressively tackling environmental problems caused by human activities. Thus the environmental permit policy from the government aims to preserve the environment, lest there be pollution and environmental damage that harms the community. The approach in this study is normative juridical with descriptive analysis specifications. The results of the study show that the implications of environmental permit policies on the environment in Indonesia are not actual permits, but are only limited to environmental approvals. Environmental permits are removed and integrated into business permits. These changes bring about the weakening of environmental instruments which are a manifestation of deviations related to environmental justice, such as licensing simplifications, strict liability disorientation, and restrictions on environmental rights: this limitation of environmental rights is in the form of limiting the degree of community participation in the EIA process, eliminating clauses for filing objections to the EIA process, and the unclear position of environmental approvals as objects of state administrative disputes. Tujuan penelitian ini adalah untuk menganalisis implikasi kebijakan izin lingkungan terhadap lingkungan hidup di Indonesia. Adapun urgensi penelitian ini mengingat bahwa kebijakan izin lingkungan merupakan alat pemerintah yang bersifat preventif mengendalikan perilaku masyarakat, dan represif menanggulangi masalah lingkungan disebabkan aktivitas manusia. Kebijakan izin lingkungan dari pemerintah bertujuan untuk melestarikan lingkungan, jangan sampai terjadi pencemaran dan kerusakan lingkungan yang merugikan masyarakat. Pendekatan dalam penelitian ini adalah yuridis normatif dengan spesifikasi deskriptif analisis. Hasil penelitian menunjukkan bahwa implikasi kebijakan izin lingkungan terhadap lingkungan hidup di Indonesia yang saat ini bukanlah izin yang sesungguhnya, namun hanya sebatas persetujuan lingkungan. Izin lingkungan dihilangkan dan diintegrasikan ke dalam izin berusaha. Perubahan tersebut membawa pelemahan instrument lingkungan hidup yang merupakan perwujudan penyimpangan terkait keadilan lingkungan yaitu seperti simplikasi perizinan, disorientasi strict liability, dan pembatasan hak lingkungan: pembatasan hak lingkungan ini berupa pembatasan derajat partisipasi masyarakat dalam proses Amdal, penghapusan klausul pengajuan keberatan terhadap proes Amdal, dan ketidakjelasan kedudukan persetujuan lingkungan sebagai objek sengketa tata usaha negara.